A new Leucoagaricus species of section Piloselli (Agaricales, Agaricaceae) from Spain - Marco Contu; Agustín Caballero; Guillermo Muñoz; Alfredo Vizzini (IMA Fungus)
The new species Leucoagaricus variicolor is described from a public park in Zaragoza, Spain, based on both morphological and molecular characters. Illustrations of fresh basidiomata in situ and of the main macro- and micromorphological features are added. Leucoagaricus variicolor belongs to section Piloselli and is compared with similar taxa.